Diabetes in Non-Hispanic White Youth: Prevalence, incidence, and clinical characteristics: the SEARCH for Diabetes in Youth Study - Bell, Ronny A. (American Diabetes Association, 2009)

(untitled)
OBJECTIVE—To investigate the incidence, prevalence, and clinical characteristics of diabetes among U.S. non-Hispanic white (NHW) youth. RESEARCH DESIGN AND METHODS—Data from the SEARCH for Diabetes in Youth Study (SEARCH study), a multicenter study of diabetes among youth aged 0–19 years, were examined. Incidence rates were calculated per 100,000 person-years across 4 incident years (2002–2005), and prevalence in 2001 was calculated per 1,000 youths. Information obtained by questionnaire, physical examination, and blood and urine collection was analyzed to describe the characteristics of youth who completed an in-person visit. RESULTS—The prevalence of type 1 diabetes (at ages 0–19 years) was 2.00/1,000, which was similar for male (2.02/1,000) and female (1.97/1,000) subjects. The incidence of type 1 diabetes was 23.6/100,000, slightly higher for male compared with female subjects (24.5 vs. 22.7 per 100,000, respectively, P = 0.04). Incidence rates of type 1 diabetes among youth aged 0–14 years in the SEARCH study are higher than all previously reported U.S. studies and many European studies. Few cases of type 2 diabetes in youth aged <10 years were found. The prevalence of type 2 diabetes (at ages 10–19 years) was 0.18/1,000, which is significantly higher for female compared with male subjects (0.22 vs. 0.15 per 1,000, P = 0.01). Incidence of type 2 diabetes was 3.7/100,000, with similar rates for female and male subjects (3.9 vs. 3.4 per 1,000, respectively, P = 0.3). High levels of abnormal cardiometabolic and behavioral risk factor profiles were common among youth with both type 1 and type 2 diabetes. For example, within each of four age-groups for youth with type 1 diabetes and two age-groups for youth with type 2 diabetes, >40% had elevated LDL cholesterol, and <3% of youth aged >10 years met current recommendations for intake of saturated fat. Among youth aged ≥15 years, 18% with type 1 and 26% with type 2 diabetes were current smokers. CONCLUSIONS—The SEARCH study is one of the most comprehensive studies of diabetes in NHW youth. The incidence of type 1 diabetes in NHW youth in the U.S. is one of the highest in the world. While type 2 diabetes is still relatively rare, rates are several-fold higher than those reported by European countries. We believe efforts directed at improving the cardiometabolic and behavioral risk factor profiles in this population are warranted.